2013
DOI: 10.1016/j.jaci.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Selective ablation of mast cells or basophils reduces peanut-induced anaphylaxis in mice

Abstract: Background Studies using c-kit mutant mast cell (MC)-deficient mice and antibody-mediated depletion of basophils suggest that both MCs and basophils can contribute to peanut-induced anaphylaxis (PIA). However, interpretation of data obtained using such approaches is complicated because c-kit mutant mice have several phenotypic abnormalities in addition to MC deficiency and basophil-depleting antibodies can also react with MCs. Objective We analyzed: (1) the changes in the features of PIA in mice after the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 58 publications
3
73
1
Order By: Relevance
“…In other models of murine food allergy, anaphylaxis can be evoked following parenteral injection of allergen, a nonphysiologic means of allergen exposure. In this setting, cells other than mast cells and molecules other than IgE have been shown to contribute to the severity of the anaphylaxis (Oettgen et al, 1994;Khodoun et al, 2009;Reber et al, 2013). In our ingestion challenge model, however, both anaphylaxis and other measures of mast cell activation are abrogated in the absence of IgE or FcεRI Mathias et al, 2011).…”
Section: Effector Roles Of Ige and Mast Cells In Food Allergymentioning
confidence: 83%
See 1 more Smart Citation
“…In other models of murine food allergy, anaphylaxis can be evoked following parenteral injection of allergen, a nonphysiologic means of allergen exposure. In this setting, cells other than mast cells and molecules other than IgE have been shown to contribute to the severity of the anaphylaxis (Oettgen et al, 1994;Khodoun et al, 2009;Reber et al, 2013). In our ingestion challenge model, however, both anaphylaxis and other measures of mast cell activation are abrogated in the absence of IgE or FcεRI Mathias et al, 2011).…”
Section: Effector Roles Of Ige and Mast Cells In Food Allergymentioning
confidence: 83%
“…Disruption of the skin barrier as occurs in atopic dermatitis, a condition associated with a high risk of food allergy in infants, leads to the development of anaphylactic food allergy in mouse models (Bartnikas et al, 2013). Together, these models have established clear requirements for IgE and mast cells in the acute allergic responses to food allergens (Bartnikas et al, 2013;Brandt et al, 2003;Reber et al, 2013).…”
Section: Effector Roles Of Ige and Mast Cells In Food Allergymentioning
confidence: 99%
“…I.v. transfer of BMCMCs also results in high levels of MCs in the spleen, whereas very few native MCs are typically found in this organ in wild type mice 23,56 . Importantly, previous reports demonstrated that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…We took advantage of the DT ablation strategy (3) by generating transgenic mice with insulin promoter-driven DT receptor (DTR) expression to confer hyperglycemia-dependent DTR expression in these mice. The analogous strategy had previously been used successfully to selectively ablate B cells (5), dendritic cells (13), mast cells (7,15), and macrophages (10) in mice. Because we used the insulin promoter for creating the DTR mice, we had to circumvent the production of DTR by pancreatic ␤-cell by using these mice as BMT donors.…”
Section: Discussionmentioning
confidence: 99%